2020
DOI: 10.51791/njap.v47i3.141
|View full text |Cite
|
Sign up to set email alerts
|

Haematological and serological response of broiler chickens to varying levels of direct fed microbes as feed additive

Abstract: Several efforts are being made to find the possibilities of utilizing Direct fed microbes (DFM) that has a potential to replace antibiotics as a result of its ability to prevent internal colonization of enteropathogenic enzymes, stimulate intestinal immunity of broiler chickens and reduce stress in animals. A studywas conducted using 120, one day-old Ross 308 broiler chicks to evaluate blood and serum chemistry response to direct fed microbes. The broiler chicks were obtained from a reputable hatchery and rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…addition, average erythrocyte size, haemoglobin amount per blood cell, and the amount of haemoglobin relative to the size of the cell per red blood cells were studied. Although, the MCV, MCH and MCHC values reported in this work were lower than broiler normal means values of 174 fL for MCV, 61pg/cell for MCH and 33 g/dl for MCHC reported by Merck (2012) for broilers, it is worthy of note that these values reported in this study are in line with the MCV, MCH and MCHC values reported for broilers by Onunkwo et al (2018), Odunitan-Waya et al (2018, Ifelayo et al (2020) and Muneer et al (2021), and within the normal ranges of 90-140fL (MCV), 33-47 pg/cell (MCH) and 26-35 g/dl (MCHC) reported for broilers by Bounous and Stedman (2000). Hence, the ability of the extracts to maintain the MCV, MCH, MCHC levels of colibacillosis infected broilers indicates that they may possess phytobiotic properties against the E. coli as well as the tendency to restore blood quality.…”
Section: Insupporting
confidence: 83%
“…addition, average erythrocyte size, haemoglobin amount per blood cell, and the amount of haemoglobin relative to the size of the cell per red blood cells were studied. Although, the MCV, MCH and MCHC values reported in this work were lower than broiler normal means values of 174 fL for MCV, 61pg/cell for MCH and 33 g/dl for MCHC reported by Merck (2012) for broilers, it is worthy of note that these values reported in this study are in line with the MCV, MCH and MCHC values reported for broilers by Onunkwo et al (2018), Odunitan-Waya et al (2018, Ifelayo et al (2020) and Muneer et al (2021), and within the normal ranges of 90-140fL (MCV), 33-47 pg/cell (MCH) and 26-35 g/dl (MCHC) reported for broilers by Bounous and Stedman (2000). Hence, the ability of the extracts to maintain the MCV, MCH, MCHC levels of colibacillosis infected broilers indicates that they may possess phytobiotic properties against the E. coli as well as the tendency to restore blood quality.…”
Section: Insupporting
confidence: 83%